ENHANCED INTERCONNECTION OF TiO2 NANOPARTICLES USING ATOMIC LAYER DEPOSITION FOR FLEXIBLE DYE-SENSITIZED SOLAR CELLS WITH PLASTIC SUBSTRATES - Kim, Boeun; Li, Yuelong; Jung, Heesuk; Kim, Jin Young; Lee, Doh-Kwon; Kim, Bongsoo; Son, Hae Jung; Kim, Do-Heyoung; Ko, Min Jae (WORLD SCIENTIFIC PUBL CO PTE LTD, 2014)
In order to improve the interconnection of TiO2 photoelectrode for the exible dye-sensitized solar cells (DSSCs) with plastic substrates, thin TiO2 layers are additionally introduced to the surface of main TiO2 nanoparticles by atomic layer deposition (ALD) at low temperature. The ALD-induced TiO2 thin layers on porous films effectively reduced the internal electrical resistance, leading to the facilitated electron transport in DSSCs. As a result, DSSCs with ALD-induced TiO2 thin layers (thickness of similar to 1.5 nm) showed better power conversion efficiency of 3.09%, which is 33% enhancement compared with that without ALD-induced TiO2 thin layers (2.32%).
Keywords: LOW-TEMPERATURE FABRICATION; ELECTRON-TRANSPORT; FILMS; PHOTOELECTRODES